FORMULASI ES KRIM SARI KEDELAI DAN PISANG AMBON SEBAGAI SELINGAN UNTUK REMAJA ANEMIA - Nur Fitriani, Melia; Gumilar, Mulus; Rahmat, Mamat; Purnawan, Asep Iwan (Poltekkes Kemenkes Bandung, 2022)
Ice cream soymilk and Ambon banana is one of the developments of food products to improve the quality of ice cream in meeting the adequacy of protein, iron and vitamin C in adolescents. Soymilk which contains the highest protein and iron content is quite high among other types of beans and Ambon banana which has high levels of vitamin.This study aims to determine the effect of the balance of soymilk and Ambon banana on organoleptic properties, protein, iron, vitamin C content, overrun, resistance. This research is an experimental study using a completely randomized design (CRD) with the balance of soymilk and Ambon banana extracts 85%: 15%, 65%: 35% and 50%: 50%. Organoleptic testing in the form of preference levels by 30 teenage panelists, protein content analysis using the Kjehldal method, iron content analysis using the spectrophotometric method, and analysis of vitamin C levels using the iodometric titration method. Data analysis using Kruskal Wallis test.The results showed that the balance of soymilk and Ambon banana had a significant effect on color and aroma (p>0.05), and had no significant effect on taste, texture and overall ice cream (p<0.05). The panelists most preferred ice cream was ice cream with a balance of soybean juice and Ambon banana 65%:35%. One serving of ice cream (100 ml) of soybean juice and the best Ambon banana can meet 6.1%, 16.2% and 27.4%, respectively, of the daily adequacy of protein, iron and vitamin C for adolescents. The ice cream overrun does not meet the standard so that further research is needed on ice cream formulations to increase the overrun.